Amazon cloud computing platform EC2 and VANET simulations. (2019) - Iqbal, Muhammad Azhar; Aleem, Muhammad; Ibrahim, Muhammad; Anwar, Saleem; Islam, Muhammad Arshad
Network simulations are resource and time intensive tasks due to the involvement of a number of factors attributable to scalability with respect to computation time, cost, and energy. Academic clouds are employed for large-scale network simulations, which require extensive capacity and intelligent resource management. This paper explores the performance efficiency of cloud solution to facilitate network researchers by proposing the utilisation of network simulator configured virtual machines. The prototype framework is executed using Amazon elastic computing cloud (EC2) Windows' instances configured with OPNET simulator. Simulation results show three significant benefits i.e., i) for scalable network simulations, consumption of considerably fewer resources in terms of simulation elapsed time, hardware resources and usage costs; ii) reduction of carbon emission leading towards sustainable IT; iii) promotion of network research by making complicated issues like simulation scalability and setup (installation or configuration) of network simulators to facilitate researchers and students.